2021
DOI: 10.3390/s21186082
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Ultra-Thin Nanocomposite Based Piezoresistive Pressure Sensors for Foot Pressure Distribution Measurement

Abstract: Foot pressure measurement plays an essential role in healthcare applications, clinical rehabilitation, sports training and pedestrian navigation. Among various foot pressure measurement techniques, in-shoe sensors are flexible and can measure the pressure distribution accurately. In this paper, we describe the design and characterization of flexible and low-cost multi-walled carbon nanotubes (MWCNT)/Polydimethylsiloxane (PDMS) based pressure sensors for foot pressure monitoring. The sensors have excellent elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Moreover, Rajendran (2021) discerned a correlation between athletes’ psychological challenges and gait imbalances [ 133 ]. By monitoring athletes’ gait distribution, potential psychological impediments can be identified, paving the way for optimized competitive performance.…”
Section: Flexible Wearable Device Product Categories In Sportsmentioning
confidence: 99%
“…Moreover, Rajendran (2021) discerned a correlation between athletes’ psychological challenges and gait imbalances [ 133 ]. By monitoring athletes’ gait distribution, potential psychological impediments can be identified, paving the way for optimized competitive performance.…”
Section: Flexible Wearable Device Product Categories In Sportsmentioning
confidence: 99%
“…However, it remains challenging to improve the sensors performance from multiple aspects simultaneously and realize the on-demand design of mechanical force sensors for specific application scenarios. As shown in Figure 1 , many applications in healthcare and diagnosis are opened up by developments of flexible mechanical force sensors, including pulse wave [ 110 , 111 , 112 , 113 , 114 , 115 ] and muscle softness detection [ 116 ], ICP and IOP measurement [ 117 , 118 , 119 ], throat and cardiac activity monitoring [ 55 , 120 ], abdomen and pulse diagnoses [ 121 , 122 ], as well as force sensing in orthotics [ 123 , 124 ], orthodontics [ 125 ] and skin-prosthesis interface [ 64 ]. While many excellent reviews of flexible pressure sensors can be found in the literature [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ], they focus mainly on the working mechanisms, material selections and device performances.…”
Section: Introductionmentioning
confidence: 99%
“…To measure pressures in the range of 1–100 atm (approximately 0.1–10 MPa), an elastomer with a high Young’s modulus is needed to avoid complete compression within the pressure range, while sensors implementing Polydimethylsiloxane (PDMS) as the matrix have had success with implenting sensors over a wide range of pressures [ 14 , 15 , 16 , 17 ], and the pressure range of interest in this work far exceeds what PDMS is capable of. The maximum Young’s modulus of PDMS (as a function of the monomer to curing agent ratio) has been shown to be 2–3 MPa [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%